2010
DOI: 10.1371/journal.pone.0009570
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alcohol Metabolism in Non-Alcoholic Steatohepatitis

Abstract: BackgroundNon-alcoholic steatohepatitis (NASH) is a serious form of non-alcoholic fatty liver disease (NAFLD), associated with obesity and insulin resistance. Previous studies suggested that intestinal bacteria produced more alcohol in obese mice than lean animals.Methodology/Principal FindingsTo investigate whether alcohol is involved in the pathogenesis of NASH, the expression of inflammation, fibrosis and alcohol metabolism related genes in the liver tissues of NASH patients and normal controls (NCs) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 38 publications
(39 reference statements)
16
145
1
4
Order By: Relevance
“…42,43). Our combined analysis, as well as a more limited study (68), demonstrated DPT upregulation in the liver of NASH patients. This finding was not confirmed in a recent cross-species transcriptomic study, which relied on a cohort stratification based on the composite NAS score; this score does not isolate the fibrosis component of the disease (69) and therefore precludes the detection of altered Dpt expression (Supplemental Figure 9).…”
Section: Discussionsupporting
confidence: 54%
“…42,43). Our combined analysis, as well as a more limited study (68), demonstrated DPT upregulation in the liver of NASH patients. This finding was not confirmed in a recent cross-species transcriptomic study, which relied on a cohort stratification based on the composite NAS score; this score does not isolate the fibrosis component of the disease (69) and therefore precludes the detection of altered Dpt expression (Supplemental Figure 9).…”
Section: Discussionsupporting
confidence: 54%
“…In 2009, our group completed the first global gene expression analysis of NASH livers and normal controls (http://www.ncbi.nlm. nih.gov/geo/query/acc.cgi?acc=GSE17470), and found that many of the alcohol and aldehyde dehydrogenases are among the most up-regulated genes in NASH livers (41). Additionally, other alcohol metabolizing mechanisms including CYP2E1 and catalase are also highly elevated in NASH livers.…”
Section: Gut Microbes Produce Alcoholmentioning
confidence: 99%
“…Overall, these studies suggest that, endotoxemia is not required in the pathogenesis of NASH. Endotoxemia may contribute to disease progression in some NASH cases, but other challenges such as gut derived alcohol (39,41), endoplasmic reticulum stress, and adipose tissue derived threats may cause NASH independently from endotoxemia. Our observations highlight the current "multi-hit" hypothesis for the pathogenesis of NASH (69).…”
Section: Possible Roles Of Lps On Metabolic Diseases and Nafld/nash: mentioning
confidence: 99%
“…The increased expression of CYP2E1 results in oxidative stress and production of ROS. The toxic metabolites of ethanol along with ROS may contribute to the development of steatohepatitis (17)(18)(19). In both human and rat liver, CYP2E1 is expressed predominantly in acinar zone 3 (18).…”
Section: Binge Alcohol Consumption Aggravates Oxidative Stress and Prmentioning
confidence: 99%